Effects of methanol on morphology and photoluminescence in solvothermal grown ZnO powders and ZnO on Si - Marín Ramírez, Oscar Alonso (2019)
ZnO nano and microstructures were obtained by solvothermal synthesis using hexamethylenetetramine (HMTA) as alkaline agent, and water, water/methanol and methanol as solvents. Two types of samples were obtained: a ZnO powder that grew at the bulk solution and ZnO on silicon substrates. The effect of the solvent on the morphology and optical emission was studied, as well as the influence of the growth zone. With increasing methanol content, the morphology changed from nanorods to nanoparticles powders, and from oriented arrangement of nanorods to thin film on silicon substrates. Important changes in photoluminescence induced by the methanol content and depending on the growth zone were also observed.